Padrões morfométricos relacionados à alimentação de Satanoperca pappaterra (Perciformes, Cichlidae) da bacia do rio Cuiabá, Estado de Mato Grosso, Brasil - uma análise ontogenética. - Cassemiro, Fernanda Aparecida da Silva (2006)
This study aimed to analyze if Satanoperca pappaterra, a neotropical fish that explore the bottom to obtain food, change its feeding habit throughout its ontogenetic development, and if morphologic (allometric) patterns are related to feeding habit and food capture. We collected 258 individuals in the Cuiabá river basin (Brazil). Diet analysis showed that S. pappaterra could be considered as a trophic generalist species. This way, the population was classified into three functional trophic groups according to the size of individuals. The smallest individuals consumed mainly microcrustaceans, the individuals of intermediate size consumed a mixed of detritus and sediment and few organisms, and the largest individuals based their diet on chironomids and annelids. Eight morphometric variables were measured in each individual, and then we used linear regression analysis to evaluate the relationship of each of these variables to the body length. For the height and width of the mouth, as well as head length, we found isometric relationship. On the other hand, we found positive allometry for the snout length and body height in relation to body length, whereas this relationship for intestine length and eye diameter showed that there was negative allometry. These measures indicate, in some amount, the behavior and feeding habit of this species.